Aquilo dos mortos que não pode ser enterrado: memória e espectro em Mia Couto - Jaqueline de Almeida Freitas (2023)
We intent to stablish an analysis of the ghosts represented in Mia Couto’s work based in the link between the concept of spectrum, developed by Jacques Derrida, and the xipoco, a characteristic figure of the magical-religious universe of the bantu african’s society. Based on the reading of three novels by the Mozambican writer, Under the frangipani (2001), Um rio chamado Tempo, uma casa chamada Terra (2002), and Confession of the Lioness (2015), we also hold a study on the hybrid identity of the ghosts and the role that this figure plays in favor of the survival memories of violence that were repressed by the hegemonic narratives. From this perspective, will be privileged discussions about the postcolonial and memory politics. Our study will be based in the Works of Jacques Derrida, Homi K. Bhabha, Walter Mignolo, Frantz Fanon, Yves Valentin Mudimbe, Achille Mbembe, Sigmund Freud, Michel Pollak, Mácio Seligmann Silva and others.